2017
DOI: 10.7326/m16-0270
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Screening in Denmark

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
59
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(60 citation statements)
references
References 23 publications
0
59
0
1
Order By: Relevance
“…Organized breast cancer screening programs were introduced in Copenhagen in 1991 and became nationalized in late 2007 but were still incomplete in 2014 26. In Denmark, unorganized and opportunistic individual‐based prostate cancer screening initiated by the patient or the doctor was frequently performed using prostate‐specific antigen 27, 28.…”
Section: Discussionmentioning
confidence: 99%
“…Organized breast cancer screening programs were introduced in Copenhagen in 1991 and became nationalized in late 2007 but were still incomplete in 2014 26. In Denmark, unorganized and opportunistic individual‐based prostate cancer screening initiated by the patient or the doctor was frequently performed using prostate‐specific antigen 27, 28.…”
Section: Discussionmentioning
confidence: 99%
“…Jørgensen et al . reported that “one in every three women aged 50 to 69 years diagnosed with breast cancer was overdiagnosed.”11 Estimation was only based on rates of non‐advanced tumors because “there was no clear compensatory decrease in the incidence of advanced cancer in older women” ( i.e ., women aged 70 to 84 years). However, almost half of the observations in the age‐group 70–84 years were from women never invited to screening or still invited despite having passed the age of 70 years.…”
Section: Discussionmentioning
confidence: 99%
“…There is a clear increase in BC incidence worldwide, concomitant to implementation of mammography [11]. However, this increase has been attributed to overdiagnosis [1,12,13], i.e. detection by screening of cancers that would not go on to cause death or would spontaneously regress [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the rate of overdiagnosis is disputed and estimates from random clinical trials suggest than less than five percent of cancers are overdiagnosed [14]. In any case, overdiagnosis does not explain the lack of efficacy of mammography in prevention of metastatic disease [6], nor why screening has not led to a reduction in the incidence of advanced BC [13] .…”
Section: Introductionmentioning
confidence: 99%